2019
DOI: 10.3233/jad-190133
|View full text |Cite
|
Sign up to set email alerts
|

Self and Informant Memory Reports in FINGER: Associations with Two-Year Cognitive Change

Abstract: Background: Subjective memory complaints (SMCs) may be the first sign of cognitive decline in aging. Objective: To examine whether SMCs reported by oneself and informant predict cognitive change over 2 years among at-risk elderly people, and to determine the relationship of different types of SMCs (prospective and retrospective memory complaints) and change in cognitive function. Methods: This investigation is part of the FINGER project, which is a multicenter randomized controlled trial aiming at preventing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Several studies showed that a higher informant report was linked to greater cognitive deficits and longitudinal cognitive or clinical decline in cognitively unimpaired (CU) older individuals [5][6][7][8][9] and patients with mild cognitive impairment (MCI) 5,[9][10][11] or Alzheimer-type dementia (AD dementia) 11 ; while other studies found no link between the informant report and the risk of cognitive or clinical decline in various settings. 6,10,12 Part of this discrepancy might reflect the fact that the informant report clinical relevance varies according to the clinical group, as shown for the self-report measure. 13 Studies are sparse regarding the association between the informant report and Alzheimer disease biomarkers; overall, they reported a link between a higher informant report and lower amyloid β42, higher p-tau/t-tau CSF levels, 4,14,15 higher global amyloid-PET 4 and parietal tau-PET, 16 and lower hippocampal volume 4,17 and temporo-parietal glucose metabolism.…”
Section: Trial Registration Informationmentioning
confidence: 99%
“…Several studies showed that a higher informant report was linked to greater cognitive deficits and longitudinal cognitive or clinical decline in cognitively unimpaired (CU) older individuals [5][6][7][8][9] and patients with mild cognitive impairment (MCI) 5,[9][10][11] or Alzheimer-type dementia (AD dementia) 11 ; while other studies found no link between the informant report and the risk of cognitive or clinical decline in various settings. 6,10,12 Part of this discrepancy might reflect the fact that the informant report clinical relevance varies according to the clinical group, as shown for the self-report measure. 13 Studies are sparse regarding the association between the informant report and Alzheimer disease biomarkers; overall, they reported a link between a higher informant report and lower amyloid β42, higher p-tau/t-tau CSF levels, 4,14,15 higher global amyloid-PET 4 and parietal tau-PET, 16 and lower hippocampal volume 4,17 and temporo-parietal glucose metabolism.…”
Section: Trial Registration Informationmentioning
confidence: 99%
“…Fogarty (2017) [ 41 ] stated that people with mild AD had more significant concerns regarding their executive functions associated with their daily lives, an opinion which was corroborated, to a lesser extent, by their informants. However, other studies indicated that only self-reported cognitive complaints predicted future cognitive changes and were associated with executive functioning, unlike informants’ reports being associated with other cognitive processes [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…People with SMC were diagnosed according to guidelines published in [ 39 ]. There is some evidence that self-reported SMC can predict future cognitive decline [ 61 ], but findings are controversial [ 62 ]. Thus, it remains unclear if the study population is relevant for AD or if SMC had other etiologies.…”
Section: Discussionmentioning
confidence: 99%